Pengelolaan Pengembangan Objek Wisata Sejarah Benteng Marlborough di Kota Bengkulu - Amalia, Anisa; Mubarak, Adil (Policy, Law and Political Research Center, 2024)
This examination is spurred by the not exactly ideal administration of the authentic vacation spot Post Marlborough in the city of Bengkulu. This exploration utilizes graphic subjective examination. The point of this examination is to decide the administration of the advancement of the authentic vacation spot Post Marlborough in the city of Bengkulu. The aftereffects of the examination show that: the management of the historical tourism development of Fort Marlborough in the city of Bengkulu using the